Chattering-free full-order recursive sliding mode control for finite-time attitude synchronization of rigid spacecraft - Song, Zhuoyue; Duan, Chao; Wang, Jianan; Wu, Qinghe (Journal of the Franklin Institute, 2019)
This paper investigates a quaternion-based finite-time cooperative attitude synchronization and tracking of multiple rigid spacecraft with a virtual leader subject to bounded external disturbances. Firstly, the communication network between followers is assumed to be an undirected graph and every follower can get a direct access to the virtual leader, by using two neighborhood attitude error signals, a novel chattering-free recursive full-order sliding mode control algorithm is proposed such that all follower spacecraft synchronize to the virtual leader in finite time. In the proposed algorithm, the sliding mode surface is constructed by two layers of sliding mode surfaces, which are called as the outer and the inner sliding mode surfaces. To achieve finite-time performance of sliding mode dynamics, the outer sliding mode surface is designed as a terminal sliding mode manifold, and the inner one is designed as a fast nonsingular terminal sliding mode manifold, respectively. Then, to reduce the heavy communication burden, a distributed recursive full-order sliding mode control law is designed by introducing a distributed finite-time sliding mode estimator such that only a subset of the group members has access to the virtual leader. Finally, a numerical example is illustrated to demonstrate the validity of the proposed results.